General publics' perception toward COVID-19 vaccines in Afghanistan, 2021 - Mir Salamuddin Hakim; Ghulam Farooq Mansoor; Ahmad Wali Walizada; Khwaja Mir Islam Saeed; Shoaib Naeemi; Fazil Ahmad Fazil (Taylor & Francis Group, 2023)
As of August 2021, less than 5% of the total population in Afghanistan has been fully vaccinated against COVID-19. Concerns remain regarding low uptake of the vaccine due to several factors. This study was conducted to understand the perception of the public on COVID-19 and its vaccines in Afghanistan. This was a formative study using qualitative method that included FGDs with vaccination target groups and KIIs, using interview guides in local languages in 12 provinces with 300 participants during May-June 2021. Verbatim transcripts were created, and a deductive thematic analysis was conducted with transcripts after the key themes and sub-themes were developed and reviewed. Totally 24 FGDs with male and female COVID-19 high-risk groups, 12 KIIs with EPI managers, and 12 KIIs with prison heads were conducted. Key themes included awareness and perception about COVID-19, its vaccination, motivators for getting vaccinated, barriers for not getting vaccinated, and sources of information. Awareness about the COVID-19 was high in urban areas compared to rural areas. Almost 60% of the participants considered the COVID-19 vaccine effective. However, participants expressed their concerns regarding rumors and misconceptions on content, source, effectiveness, and side effects of the vaccine in their communities. Based on the study results, many participants expressed accurate knowledge about the COVID-19 disease and its vaccines. Significant barriers including misinformation, conspiracy theories, and fear of side effects persist. Collaboration between stakeholders and increasing awareness and engagement of communities about the benefits and effectiveness of the vaccines should be considered crucial.